A Pc-Based Freehand Three-Dimensional Ultrasound. - Aziz, Shalihatun Azlin; Mat Isa, Nor Ashidi; Ngah, Umi Kalthum; Ibrahim, Haidi; Aziz, Mohd Ezane (2007)

(untitled)
Breast cancer is the number one killer disease among women in Malaysia. In the diagnosis of breast cancer, breast ultrasound examination is commonly used as a supplement to mammography.